Introduction to multimodal analysis - Machin, David, 1966-; Ledin, Per (London, England : Zed Books, 2020)
"Providing a clear model that students can follow, the second edition of Introduction to Multimodal Analysis contains fresh, contemporary examples ranging from product packaging and website layouts to film adverts and public spaces. It also features two new chapters on texture and diagrams, as well as a helpful image index that demonstrates how multimodal texts can be analysed from different perspectives. With chapter summaries, student activities and a companion website hosting the images in full colour, this book remains an essential guide for students studying multimodailty within visual communication."--
Introduction -- 1. What is multimodal analysis? -- 2. Pictures and images -- 3. Modality: Experiencing the world through images -- 4. The meaning of colour in visual design -- 5. The meaning of typography -- 6. Textures and materiality -- 7. Composition and page layout -- 8. Diagrams and flow charts.
Previous edition: London: Hodder Arnold, 2007.
Includes bibliographical references (pages 219-223) and indexes.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Visual communication; Mass media and language; Modality (Linguistics); Multimedia systems; Discourse analysis; Electronic books